Migraine treatment: the doors for the future are open, but with caution and prudence - Abouch V. Krymchantowski; Ana Gabriela Ferreira Krymchantowski; Carla da Cunha Jevoux (Arquivos de Neuro-Psiquiatria)
ABSTRACT Migraine is a burdensome disorder. Current treatments are far from ideal. Recent knowledge has been indicating targets whose antagonism may improve efficacy. It is particularly true with the calcitonin gene-related peptide (CGRP) and the monoclonal antibodies anti-CGRP can interfere with this pathway and decrease the frequency of migraine attacks. Erenumab, fremanezumab and galcanezumab have recently been approved and eptinezumab is likely to be, soon. Although efficacy figures were not spectacular, tolerability and potential higher adherence were noteworthy. However, caution must be exercised. The time frame after the studies was limited to three years and dose administration was restricted to three-monthly doses. The CGRP is present throughout the human body and migraine is a life-long disease, often requiring treatment for decades. It is not known whether this favorable profile can be maintained or will be safe in pregnant women or adolescents. In addition, there were deaths during the studies, which may have happened without a clear relationship. New treatments are welcome, but caution is warranted.